1978
DOI: 10.1136/hrt.40.11.1262
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive assessment of left ventricular function in myotonic muscular dystrophy.

Abstract: Myotonic muscular dystrophy is a diffuse systemic disorder, which is inherited as an autosomal dominant trait, with appearance in both sexes, generally late onset of symptoms, and slowly progressive evolution. The clinical picture may include involvement of skeletal and cardiac muscle, cataracts, premature frontal baldness, bone changes, testicular atrophy, other mild endocrine abnormalities, and mental deterioration.Evidence of cardiac disease in patients with myotonic dystrophy is usually found in the electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…In 24% of patients we have shown Dopp ler abnormalities that conformed to a pattern of impaired left ventricular relaxation. These findings are supported bv previous M-mode échocardiographie studies [8,9] that showed reduced maximal diastolic endocardial velocity and decreases in the left ventricular peak diastolic length ening rate in patients with myotonic dystrophy and with out clinically apparent heart failure. On the contrary, a recent study [14] showed a Doppler pattern of abnormal relaxation (early to atrial peak velocity ratio < 1 and timevelocity integral of early velocity curve to atrial curve ratio <1.5) in only 3 of 42 unselected patients with myo tonic dystrophy and in only 1 patient diastolic dysfunc tion was related to a myocardial dystrophic disease.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In 24% of patients we have shown Dopp ler abnormalities that conformed to a pattern of impaired left ventricular relaxation. These findings are supported bv previous M-mode échocardiographie studies [8,9] that showed reduced maximal diastolic endocardial velocity and decreases in the left ventricular peak diastolic length ening rate in patients with myotonic dystrophy and with out clinically apparent heart failure. On the contrary, a recent study [14] showed a Doppler pattern of abnormal relaxation (early to atrial peak velocity ratio < 1 and timevelocity integral of early velocity curve to atrial curve ratio <1.5) in only 3 of 42 unselected patients with myo tonic dystrophy and in only 1 patient diastolic dysfunc tion was related to a myocardial dystrophic disease.…”
Section: Discussionsupporting
confidence: 78%
“…Most studies, however, demonstrated that demonstrate impairment of diastolic performance [2,12]; others [8,9] showed abnormalities in left ventricular relaxation. Recently, a study assessing the relation be tween the severity of cardiac involvement and the myo tonic dystrophy genotype [14] reported that Doppler echocardiographic indexes of left ventricular tilling are normal in patients with myotonic dystrophy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac involvement is usually characterized by conduction system abnormalities with prolonged PR interval, frequent bradyarrhythmias and increased risk of sudden death [2][3][4]. Despite some controversial results [5,6], it is known that patients with myotonic dystrophy may develop a specific cardiomyopathy and symptoms of heart failure [7,8], while only subclinical left ventricular (LV) diastolic dysfunction is detectable in the early stages of disease [9][10][11][12]. In this view, and because of a very variable phenotypic expression of the International Journal of Cardiology 118 (2007) 227 -232 www.elsevier.com/locate/ijcard disease, the detection of early markers of cardiac involvement may be crucial for an appropriate management of patients affected by MD [13].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac manifestations reflect selective disturbances of conduction system [2,3,5,7,9,11,13] rather than myo cardium [3,5,13,14,17]. The most com mon electrocardiographic abnormalities are sinus bradycardia, prolongation of P-R in terval and intraventricular conduction dis turbances; high-degree atrioventricular block and severe arrhythmias may also oc cur, which could be responsible for syncope and sudden death [4,10,15,16].…”
Section: Introductionmentioning
confidence: 99%